American whitelash : a changing nation and the cost of progress - Lowery, Wesley, 1990- (Mariner Books, 2023)
Interweaving deep historical analysis with gripping firsthand reporting on both victims and perpetrators of violence, a Pulitzer Prize-winning journalist charts the return of the American cycle of racial progress and white backlash and how the federal government has failed to intervene.